L’interesse “non per forza” superiore del minore - Giuseppe Recinto (Democrazia e Diritti Sociali)
Taking into account the relational relevance of parental responsibility, as well as the indications derivable from domestic jurisprudence and the European Court of Human Rights concerning the so-called new parenting, the work aims to critically review the opposing orientations aimed at configuring the child’s interest either as a ‘tyrant right’ or, on the contrary, as a ‘viaticum for the aspirations’ of adults.